2011
DOI: 10.1111/j.1752-4571.2010.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes in genotypic frequencies at thePantophysinlocus in Atlantic cod (Gadus morhua) in Icelandic waters: evidence of fisheries-induced selection?

Abstract: The intense fishing mortality imposed on Atlantic cod in Icelandic waters during recent decades has resulted in marked changes in stock abundance, as well as in age and size composition. Using a molecular marker known to be under selection (Pan I) along with a suite of six neutral microsatellite loci, we analysed an archived data set and revealed evidence of distinct temporal changes in the frequencies of genotypes at the Pan I locus among spawning Icelandic cod, collected between 1948 and 2002, a period chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 58 publications
3
67
1
Order By: Relevance
“…Pan I AB heterozygotes were intermediate in length of the 2 homozygotes. Similar features were recently reported from Icelandic waters (Jakobsdóttir et al 2011), although growth−genotype relations there have previously been reported to vary among spawning sites (Jónsdóttir et al 2008). Reports on individual length in NCC and ANC populations, classified by otolith typing, showed no difference in growth between the 2 populations (Berg & Albert 2003).…”
Section: Genotype−length Correlationssupporting
confidence: 62%
See 1 more Smart Citation
“…Pan I AB heterozygotes were intermediate in length of the 2 homozygotes. Similar features were recently reported from Icelandic waters (Jakobsdóttir et al 2011), although growth−genotype relations there have previously been reported to vary among spawning sites (Jónsdóttir et al 2008). Reports on individual length in NCC and ANC populations, classified by otolith typing, showed no difference in growth between the 2 populations (Berg & Albert 2003).…”
Section: Genotype−length Correlationssupporting
confidence: 62%
“…The coexistence of migratory and stationary stocks of Atlantic cod has been reported from different regions of the North Atlantic (e.g. Robichaud & Rose 2004, Jakobsdóttir et al 2011), but nowhere so well defined and with such abrupt differences at the Pan I locus as between ANC and NCC.…”
Section: Pan I -Validity and Selective Constraintsmentioning
confidence: 99%
“…Fisheries pose strong predation pressure on fish populations and may cause evolutionary change [72]. Two recent studies indicate fisheries effects on the relative frequencies of inshore (Pan I AA ) and offshore (Pan I BB and Pan I AB ) genotypes in the Icelandic Atlantic cod population [9,18]. The frequency of the offshore Pan I B allele in the historical samples is low (table 2) in comparison with samples from modern-day inshore spawning stock [9].…”
Section: Discussionmentioning
confidence: 99%
“…Archived material from fisheries surveys has revealed the history of many commercial fish populations, although the samples commonly include only few generations [17][18][19]. Atlantic cod vertebrae have accumulated at historical fishing sites in the North Atlantic since the beginning of commercial fishing [20,21] and in Iceland since the early settlement [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be borne in mind that even if fisheries-induced changes in life histories did not affect population growth rate directly, they may still affect a population's ability to cope with environmental fluctuations [59]. In cod, for instance, a population of early-and small-maturing individuals has been hypothesized to be more vulnerable to climate change [60,61]. All such features need to be carefully accounted for when evaluating conservational consequences of anthropogenic evolution [62].…”
Section: Discussionmentioning
confidence: 99%